HEAT STRESS CHALLENGES AND MITIGATION STRATEGIES IN INDONESIAN SMALLHOLDER DAIRY FARMS: A BRIEF REVIEW - Ahmad Nasihin; Dwirana Malik Fajar (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2026)
This review synthesizes the impacts of heat stress and assesses viable mitigation strategies for smallholder dairy farms in Indonesia. In such systems, heat stress can be detected early through observable physiological and behavioral alterations. Clinical indicators such as an increased respiratory rate (exceeding 60 breaths per minute), reduced feed intake, and restless behavior serve as early warning signs that are recognizable by farmers. The effects of heat stress are complex and detrimental, including reductions in milk production by 10–20% or more, increased reproductive disorders with conception rates below 20%, as well as heightened disease susceptibility and elevated production costs. Mitigation strategies for heat stress in smallholder dairy systems encompass three principal aspects: (1) housing and environmental management via barn orientation, roof design and height, natural ventilation, suitable building materials, and shade vegetation as passive cooling methods; (2) feed and water management through increased dietary energy density and provision of drinking water ad libitum; and (3) daily activity management by scheduling feeding and milking during cooler periods. Building upon these approaches, pragmatic and cost-effective strategies are vital for maintaining productivity in smallholder dairy systems, while targeted empowerment of farmers through practical support can enhance production by up to 16% and markedly diminish the impacts of heat stress. According to this review, context-specific mitigation of heat stress, supported by farmer empowerment and practical assistance, is crucial for ensuring sustained productivity and resilience in smallholder dairy farming systems within tropical regions.